Alterations in White Matter and Total Brain Volumes Underlie Genetic Risk of Hydrocephalus. (16th November 2020) - Hale, Andrew T; Wellons, John C; Limbrick, David D; Schiff, Steven J; Gamazon, Eric R
Abstract: INTRODUCTION: Although many genes have been associated with hydrocephalus, the pathophysiological effects of these genes are largely unknown. Recent studies have suggested that hydrocephalus is caused, at least in part, by abnormal neurogenesis which may lead to alterations in white matter and total brain volume. Here we perform a genome wide association study (GWAS) to identify genes associated with hydrocephalus and their relationship with white matter and total brain volumes. METHODS: Using PrediXcan (Gamazon et al. Nature Genetics 2018), we conducted a GWAS to identify genes associated with pediatric hydrocephalus in BioVU (287 cases and 18, 740 controls). We then used PrediXcan to identify genes associated with white matter and total brain volumes using MRI data from 8, 428 individuals in the UK Biobank- controlled for age, sex, and genetic ancestry using 40 principal components. Q-Q plots were generated to visualize the relationship between hydrocephalus-associated genes and their association with white matter or total brain volume. RESULTS: We identify maelstrom (MAEL), a gene involved in DNA transposon and epigenetic regulation, as a genome-wide predictor of hydrocephalus. MAEL expression is associated with decreased white matter and total brain volumes (Bonferroni-adjusted p< 0.05), suggesting that MAEL may confer risk of hydrocephalus through regulation of brain structure. Among 158 genes nominally-associated (p< 0.05) with hydrocephalus, compared to a random selection of genes, we observe a significant enrichment for genes associated with white matter volume and total brain volume. These data suggest that genetic susceptibility to hydrocephalus may be mediated by alterations in brain structure and/or growth. CONCLUSION: Our data reveals insights into the genetic architecture and pathophysiological basis of hydrocephalus. These results suggest that hydrocephalus-associated genes may exert their effects, at least in part, through regulation of brain structure and/or growth.